Pengaruh Islamic Branding Dan Islamic Service Quality Terhadap Loyalitas Nasabah Bank Muamalat Indonesia Dengan Customers Satisfaction Sebagai Variabel Intervening - Fathur Rahman Baihaki; Tri Inda Fadhila Rahma; Juliana Nasution (LPPM Universitas Labuhanbatu, 2026)
This study aims to determine the effect of Islamic branding and Islamic service quality on customer loyalty at Bank Muamalat Indonesia with customer satisfaction as an intervening variable. This type of research is a quantitative research with secondary data sources, by distributing research questionnaires to respondents. The data for this research were taken from the answers of the research respondents who in this study were the customers of Bank Muamalat Indonesia who are domiciled in the Panyabungan City area. Processing techniques and data analysis using Descriptive Statistical Analysis, using SmartPLS version 4 software. The results show that the Islamic Branding variable has a direct influence on the Customer Satisfaction variable. Islamic Service Quality has a direct influence on the Customer Satisfaction variable. Islamic Branding has a direct influence on the Loyalty variable. Islamic Service Quality has no direct influence on the Loyalty variable. Customer Satisfaction has no direct effect on the Loyalty variable. Islamic Branding has no effect on Loyalty through Customer Satisfaction. Islamic Service Quality has no influence on Loyalty through Customer Satisfaction.